The Potential of Various Types of Decomposers on the Effectiveness of Palm Oil Fruit Bunch (EFB) Composting and a Study of Socio-Economic Conditions in the Village of Lubuk Ogung - Rizka Utami; Rahman Karnila; Deviona Deviona (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
Empty fruit bunches (EFB) are the main solid waste product of the palm oil industry and have great potential to be processed into high-value organic fertilizer. However, the natural decomposition process is very slow. This study aims to analyze the effectiveness of several types of decomposers (EM-4, Eco-enzyme, M-21, and MSG-3) in accelerating the TKKS composting process and to identify the socio-economic conditions and perceptions of the Lubuk Ogung Village community regarding community-based waste management. The method used was a mixed-methods design, with a completely randomized design (CRD) and three replicates for technical analysis and in-depth interviews for social aspects. The parameters observed included the C/N ratio, organic C, nitrogen, phosphorus, and potassium. The results showed that Eco-enzyme and M-21 were the most effective decomposers, producing final C/N ratios of 16.44 and 17.25, respectively, which meet the SNI 7763:2024 standard. Socially, the community showed a positive perception of TKKS composting, though they still faced obstacles in technical knowledge, market access, and program sustainability. These findings indicate that the application of decomposer technology, particularly Eco-enzyme, has the potential to strengthen waste management and promote community empowerment through circular economy practices at the village level.